Associations of ApoAI and ApoB–Containing Lipoproteins With AngII–Induced Abdominal Aortic Aneurysms in Mice. Issue 8 (August 2015) - Liu, Jing; Lu, Hong; Howatt, Deborah A.; Balakrishnan, Anju; Moorleghen, Jessica J.; Sorci-Thomas, Mary; Cassis, Lisa A.; Daugherty, Alan
Abstract : Objective—: Dyslipidemia is implicated in abdominal aortic aneurysms (AAAs) in humans and angiotensin (Ang) II–infused mice. This study determined effects of major lipoprotein classes on AngII-induced AAAs using multiple mouse strains with dietary and pharmacological manipulations. Approach and Results—: Western diet had minor effects on plasma cholesterol concentrations and the low incidence of AngII-induced AAAs in C57BL/6J mice. Low incidence of AAAs in this strain was not attributed to protection from high-density lipoprotein, because apolipoprotein (apo) AI deficiency did not increase AngII-induced AAAs. ApoAI deletion also failed to alter AAA occurrence in hypercholesterolemic mice. Low-density lipoprotein receptor−/− mice fed normal diet had low incidence of AngII-induced AAAs. Western diet feeding of this strain provoked pronounced hypercholesterolemia because of increased apoB-containing lipoproteins with attendant increases of atherosclerosis in both sexes, but AAAs only in male mice. ApoE-deficient mice fed normal diet were modestly hypercholesterolemic, whereas this strain fed Western diet was severely hypercholesterolemic because of increased apoB-containing lipoprotein concentrations. The latter augmented atherosclerosis, but did not change the high incidence of AAAs in this strain. To determine whether reductions in apoB-containing lipoproteins influenced AngII-induced AAAs, ezetimibe was administered at a dose that partially reduced plasma cholesterol concentrations to ApoE-deficient mice fed Western diet. This decreased atherosclerosis, but not AAAs. This ezetimibe dose in ApoE-deficient mice fed normal diet significantly decreased plasma apoB-containing lipoprotein concentrations and reduced AngII-induced AAAs. Conclusions—: ApoB-containing lipoproteins contribute to augmentation of AngII-induced AAA in male mice. However, unlike atherosclerosis, AAA occurrence was not correlated with increases in plasma apoB-containing lipoprotein concentrations. Abstract : Supplemental Digital Content is available in the text.